Influence of in vitro adaptation to benzylpenicillin on biological properties of Staphylococcus aureus - Peretyatko, Olena; Yagnyuk, Yulia; Sklyar, Nadia; Krestetska, Svitlana; Bolshakova, Galina; Kholodna, Tatiana (Annals of Mechnikov’s Institute, 2023)
Introduction. Antimicrobial resistance is a global problem that equally affects both highly developed countries and those that are developing. The formation and spread of antibiotic resistance to microorganisms are the unavoidable consequence of the evolutionary process and one of the manifestations of the bacteria adaptation to unfavorable conditions to exist. To contain and overcome antibiotic resistance is necessary to study the process of it’s evolution, identify factors that contribute the implementation of this process and establish the most significant factors of influence to increasing or decreasing the level of resistance. The aim of the work was to study the biological properties of Staphylococcus aureus with resistance to benzylpenicillin, formed in vitro. Materials and methods. Research objects: 12 different groups of museum strains of Staphylococcus aureus that were sensitive to antibiotics from the museum collection of the microorganisms in NU "IMI NAMN". The sensitivity of microbial cultures to antibiotics was determined by the disk-diffusion method of Keurby-Bauer and by the method of serial dilutions in broth. Staphylococci’s adaptation to benzylpenicillin was carried out by passage on Mueller-Hinton agar with increasing of the antibiotic concentrations, starting with subbactericidal. The kinetics of strain growth was studied by growing a microbial suspension with a density of 1.0 according to the McFarland scale in Muller-Hinton broth at a temperature of 37 ºС, with the determination of the optical density of the studied samples after 0.5, 1, 2, 3, 4, 6, 8, 10, 12, 24, 36 and 48 hours of cultivation using a Densi-La-Meter device (wavelength 540 nm). Biochemical properties of staphylococci were determined using the API system ID 32 STAPH. Statistical processing of the obtained data was carried out using Microsoft Excel 2007, STATISTICA 6.1 computer programs (StatSoft Inc., USA, serial number - AGAR909E415822FA). Research and discussion. During cultivation on the environment with increasing concentrations of the antibiotic, there was observed a change in the nature of the growth of the studied strains – the prevalence of D-form colonies with a size of 1-1.5 mm, the suppression of the ability to form pigments and the decrease of number of colony-forming units (in comparison with the growth indicators of the strains on the environment without the antibiotic). The negative impact of the adaptive selection of resistance to benzylpenicillin on staphylococci was also confirmed by studies of the growth kinetics of the studied strains of S. aureus: lengthening of the lag-phase to 3 hours against 0.5 hours in the control. And a decrease in the maximum values of growth indicators in the exponential phase to 3.15 OD540 , versus 5.65 OD540 in the control (p<0.05). According to the results of studying the antibiotic sensitivity of the adapted to benzylpenicillin S. aureus in four strains was found cross-resistance in various combinations to other groups of antibiotics – to macrolides (MIC of erythromycin - from 2 μg/ml to 4 μg/ml), to tetracyclines (MIC of tetracycline - from 4 μg/ml to 8 μg/ml; MIC of doxycycline – from 2 μg/ml to 4 μg/ml), to aminoglycosides (MIC of gentamicin – 2 μg/ml, MIC of amikacin – 16 μg/ml, MIC of tobramycin – 2 μg/ml ) and to chloramphenicol (MIC – 16 μg/ml). When the strains that were adapted to high concentrations of benzylpenicillin were cultivated in an environment without the antibiotic, there was a gradual (from 8 to 14 passages) restoration of the lost biological properties. Therefore, in our opinion, resistance to antibiotics in aberrant forms of staphylococci is associated with the formation of a temporary phenotype, which reverts to a sensitive one in the absence of selective pressure. The research at the molecular genetic level is required for a more detailed study of the mechanisms of acquisition of antibiotic resistance in vitro. In our opinion, found phenotypic differences of S. aureus subpopulations, that adapted to high concentrations of benzylpenicillin, should be considered as a morpho-functional reorganization of bacterial cells under the influence of antibacterial compounds. The data we obtained are consistent with the positions of other researchers, who consider the bacterial population as a dynamic self-regulating heteromorphic and polyfunctional system with a high adaptation potential, aimed at preserving the species. Conclusion. According to the results of the conducted research, it was established that the formation of resistance to benzylpenicillin for staphylococci in vitro was accompanied by a decrease in growth properties, a loss of the ability to form pigments, and also a change in sensitivity to other groups of antibiotics. Keywords. Museum strains, Staphylococcus aureus, adaptation to benzylpenicillin in vitro, antibiotic sensitivity, biological properties.